Penerimaan Sistem Informasi Berbasis Teknologi oleh Karyawan PT. Merry’s Tour and Travel Menggunakan Aplikasi Quickbooks - Riani, Ni Wayan Desi; Rasmini, Ni Ketut (E-Jurnal Akuntansi; Vol 30 No 2 (2020), 2020)
This research is intended to find out how the employee acceptance of the QuickBooks application system tested by Merry's Tour and Travel by using the Technology Acceptance Model (TAM). This study uses a population of all management and employees of Merry’s Tour and Travel. Determination of samples usingpurposive sampling techniques and the samples that met the criteria was 34 respondents. The data collection method uses a survey method with a questionnaire. Data were analyzed using Structural Equation Model (SEM), namely Partial Least Square (PLS). Based on the results of the analysis found that the variables of top management commitment, selft-efficacy, and perceived usefulness affect the acceptance of the QuickBooks information system at PT. Merry’s Tour and Travel. This indicates that the process of transition from manual systems to QuickBooks information systems cannot be fully explained by the Technology Acceptance Model. Keywords: Perceived Ease Of Use; Perceived Usefulness; Attitude Toward Using; Behavioral Intension To Use; Technology Acceptancemodel (TAM).